Seleksi ketahanan beberapa varietas unggul kedelai terhadap serangan hama kepik hijau (Nezara viridula L.) - Nanda Faraz Ayu; Suharto . (Department of Plant Protection, Faculty of Agriculture, Universitas Jember - Indonesia, 2020)
Green stink bug (Nezara viridula L.) is a pod-sucking pest that can cause losses of up to 80%. The use of resistant varieties is an initial control effort that can be reduced or prevent losses due to green stink bug attacks on soybean plants. This study aims to determine the resistance of some soybean varieties to the attack of green stink bug (N. viridula). This study used a completely randomized design (CRD) with 5 treatments and 5 replications. The treatment used 5 soybean varieties namely V1 = Dega 1, V2 = Devon 1, V3 = Dena 1, V4 = Deja 1, V5 =. Detap 1. Each experimental unit is covered and invested 5 stink bug nymphs third instar. Based on the results, showed that Deja 1 and Detap 1 varieties are the best varieties to suppress the percentage of attacks and are included in the category of plants resistant to N. viridula, and have a significant affect to productivity higher than other varieties. Trichome density, hardness and skin thickness of pods significantly affect to the percentage of N. viridula attack so that it is included in the mechanism of antixenosis resistance.